The art of happy moving : how to declutter, pack, and start over while maintaining your sanity and finding happiness - Wenzke, Ali (William Morrow, an imprint of HarperCollins, 2019)
In this book based on her popular blog, The art of happy moving, moving pro Ali Wenzke delivers a comprehensive, step-by-step resource for every phase of the moving process. Ali shares invaluable anecdotes from her many moves, and packs each chapter with a wealth of information and ingenious tips (Did you know that if you have an extra-large welcome mat at the entrance of your home, it's more likely to sell?). Ali also includes checklists for packing and staging, and agendas for the big moving day. Whether you're a relocating professional, newly married, a family with kids and pets, or a retiree looking to downsize, The Art of Happy Moving will help you discover ways to help make your transition an easier one--and be even happier than you were before.